THE WELDABILITY OF THE STEEL WITH HIGH MANGANESE - Schmidová, Eva; Hlavaty, Ivo; Hanus, Petr (My University, 2016)
Nowadays one of the most important parts, which are used in railway industry, are crossings, and principally the dynamic component of the operation exposures. A Mangalloy, also called as manganese steel or Hadfield steel, is a steel with alloys containing an average 13% of manganese and is unique for the reason that it combines high toughness and ductility with great work-hardening capacity. The wear resistance before the contact wear depends on the level of the surface hardening intensity, and the hardening process during operation consequently. For the reason is that abrasion resistance is proper to increase the carbon level above 1.4% and moreover, it could cause a problem in obtaining a homogenous austenitic structure which would be sufficiently free of carbide bordered grains.
Svařitelnost vysocemanganové oceli
Keywords: Weldability, Hadfieldova ocel, Railway; svařitelnost, Hadfieldova ocel, kolejnice